2011
DOI: 10.1097/hnp.0b013e3182157c4a
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Asymptomatic and Symptomatic Peripheral Arterial Disease and Peripheral Arterial Disease Risk Factors in the US Population

Abstract: The National Health and Nutrition Examination Survey 2003 to 2004 data set was utilized to examine trends and differences of individuals with asymptomatic and symptomatic peripheral arterial disease (PAD) and PAD risk factor variables, determined by Ankle-Brachial Index measurement. A descriptive secondary data analysis was conducted by using the variables age, gender, hypertension (ie, systolic blood pressure and diastolic blood pressure), dyslipidemia (ie, high-density lipoprotein and low-density lipoprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 45 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Traditional lipid parameters, such as abnormal rates of high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C), are common risk factors for PAD [ 5 ]. Notably, an increasing number of studies have indicated the development and progression of atherosclerosis under conditions of abnormal nontraditional lipid profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional lipid parameters, such as abnormal rates of high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C), are common risk factors for PAD [ 5 ]. Notably, an increasing number of studies have indicated the development and progression of atherosclerosis under conditions of abnormal nontraditional lipid profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies of the prevalence of PAD in the general population indicate that many cases of PAD will not exhibit overt symptoms of PAD such as intermittent claudication [36,37]. In people with heart failure, it could be expected that due to functional limitations, many people may not ambulate to the extent to which symptoms of PAD occur, thereby precluding identification of PAD in this patient group.…”
Section: Discussionmentioning
confidence: 98%
“…The prevalence of PAD is increasing worldwide, and DM is an important risk factor for PAD [22,23]. Most patients with PAD are asymptomatic, but they have elevated risk for mortality [22][23][24]. In Taiwan, annual screening for foot complications is recommended in the clinical guidelines and in the P4P program for patients with DM [13,25].…”
Section: Discussionmentioning
confidence: 99%